2009
DOI: 10.1148/radiol.2493071483
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymph Nodes Suspicious for Breast Cancer Metastasis: Sampling with US-guided 14-Gauge Core-Needle Biopsy—Clinical Experience in 100 Patients

Abstract: Axillary lymph nodes with abnormal US findings can be sampled with high accuracy and without major complications by using a modified 14-gauge CNB technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(134 citation statements)
references
References 29 publications
7
120
0
7
Order By: Relevance
“…Ultrasound is neither sufficiently sensitive nor specific to be used alone; in patients with indeterminate cortical thickening in the range of 2-4 mm, it is essential to assess whether such patients have involved nodes by FNAC or core biopsy. [20][21][22][23] The majority of surgeons continue to perform ANC which is an appropriate treatment for involved axillary nodes. Axillary radiotherapy is another option for involved nodes, and this is used in some centres and has been shown to produce good long-term disease control rate.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is neither sufficiently sensitive nor specific to be used alone; in patients with indeterminate cortical thickening in the range of 2-4 mm, it is essential to assess whether such patients have involved nodes by FNAC or core biopsy. [20][21][22][23] The majority of surgeons continue to perform ANC which is an appropriate treatment for involved axillary nodes. Axillary radiotherapy is another option for involved nodes, and this is used in some centres and has been shown to produce good long-term disease control rate.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is a simple and well-accepted method to examine axillary and non-axillary lymph nodes associated with breast cancer. Recent publications have reported that routine axillary US combined with cytology or core biopsy is an effective method to evaluate lymph node metastases prior to surgery [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Thus, pretreatment axillary US for early breast cancer patients and needle sampling of morphologically abnormal lymph nodes are now widely recommended [36].…”
Section: Background and Objectivementioning
confidence: 99%
“…It is moderately sensitive especially when morphological criteria's are used to detect axillary metastasis [8,9]. However, Ax US is subjective and the experience of the Radiologist is important for the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%